[OP.2C.02] ENDOGENOUS OUABAIN AS A BIOMARKER OF HEART FAILURE AND A PREDICTOR OF MORTALITY AFTER CARDIAC SURGERY. (September 2016) - Pozzoli, S.; Simonini, M.; Messaggio, E.; Casamassima, N.; Bignami, E.; Zagato, L.; Lanzani, C.; Manunta, P.
Abstract : Objective: Cardiovascular diseases remain the main cause of mortality and morbidity worldwide. The identification of subjects with increased risk of developing new cardiovascular events remains a priority in order to guide treatments and determine individual prognosis. Biomarkers are useful tools that are able to help physicians in decision-making. Our aim is to investigate Endogenous Ouabain (EO), an adrenal stress hormone with hemodynamic effects, as a valuable biomarker of heart failure. Design and method: In a population of more than 800 patients undergoing elective cardiac surgery, we have investigated the relationships between EO with well known and codified markers of heart failure. We also explored the predictive power of this biomarker for 30-days morality after cardiac surgery. Results: EO was found to be correlated negatively with left ventricular EF (p = 0.001), positively with Cardiac End Diastolic Diameter (p = 0.047) and positively with plasmatic NT-proBNP level (p = 0.02). Moreover, a different plasmatic EO level (both preoperative and postoperative) was found according to NYHA class (p = 0.013). Finally, a higher EO level in the immediate post-operative time was indicative of a more severe cardiological condition and it was associated with increased perioperative mortality risk (p = 0.023 for 30-days morality). Conclusions: Our data suggest that preoperative and post-operative plasmatic EO level identifies patients with a more severe cardio-vascular presentation at baseline. These patients have a higher risk of morbidity and mortality after cardiac surgery.